PERANCANGAN DAN IMPLEMENTASI PHOTOSTOCK DI SEKOLAH SMP CHARITAS BATAM DENGAN PENERAPAN METODE 4D (DEFINE, DESIGN, DEVELOP, DISSEMINATE) - Winsley, Winsley W; Deli, Deli D (Universitas Lampung, 2024)
Charitas Batam Junior High School, an A accredited institution in Batam City, Riau Islands, was established in 2007 with a vision of providing transformative, compassionate, and fraternal education. In order to maintain its commitment to delivering innovative and high-quality education, the school is currently facing challenges concerning the insufficient quality and variety of suitable photo stock, necessitating updates. This study aims to enhance the school's operational sustainability through the enhancement by creating a new photostock repository, which will be applies the 4D method (Define, Design, Develop, Disseminate) and stored in a Google Drive folder presented as .jpg format. The photostock design process involves the use of Adobe Photoshop 2021 and Adobe Lightroom Classic software. The implementation of the photostock is expected to streamline the school's operational processes.